THE ROLE OF VILLAGES IN INTEGRATED STUNTING PREVENTION AND REDUCTION: (Juridical Review of The Working Area Bandarharjo Public Health Center North Semarang District) - Hastuti, Anita Widi; Supriyadi, Supriyadi; Susianto, Susianto (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
This research aims to investigate the contribution of communities in the North Semarang sub-district to preventing and reducing integrated stunting. It also seeks to identify the challenges encountered in these efforts. This research demonstrates that villages play a crucial role in preventing and reducing stunting in the Bandarharjo Community Health Centre Working Area, North Semarang District. This is in accordance with Presidential Regulation of the Republic of Indonesia Number 72 of 2021 and Semarang Mayor Regulation Number 45 of 2023. City of Semarang Regulation No. 27 of 2022 aims to speed up the reduction of stunting in Semarang by implementing a comprehensive plan that includes maternal and child health interventions, nutritional counselling, clean water and sanitation provision, and social protection services. Obstacles in preventing and reducing stunting in Bandarharjo village include inadequate socialisation about different communities' responses to stunting and insufficient provision of food and vitamin supplements for intervention activities. Society's culture and ideas often attribute a child's small stature to inheritance from their parents.